Permian exhumation of the Montagne Noire core complex recorded in the Graissessac‐Lodève Basin, France. (4th July 2016) - Pfeifer, Lily S.; Soreghan, Gerilyn S.; Pochat, Stéphane; Van Den Driessche, Jean; Thomson, Stuart N.
Abstract: The paleogeographic reconstruction of the Variscan Mountains during late Carboniferous‐Permian post‐orogenic extension remains poorly understood, owing to the subsequent erosion and/or burial of most associated sedimentary basins during the Mesozoic. The Graissessac‐Lodève Basin (southern France) preserves a thick and exceptionally complete record of continental sedimentation spanning late Carboniferous through late Permian time. This section records the localized tectonic and paleogeographic evolution of southern France in the context of the low‐latitude Variscan Belt of Western Europe. This study presents new detrital zircon and framework mineralogy data that address the provenance of siliciclastic strata exposed in the basin. The ages and compositions of units that constitute the Montagne Noire metamorphic core complex (west of the basin) dictate the detrital zircon age populations and sandstone compositions in Permian strata, recording rapid exhumation and unroofing of the Montagne Noire dome. Cambrian‐Archean zircons and metamorphic lithic‐rich compositions record derivation from recycled detritus of the earliest Paleozoic sedimentary cover and Neoproterozoic‐early Cambrian metasedimentary Schistes X, which formerly covered the Montagne Noire dome. Ordovician zircons and subarkosic framework compositions indicate erosion of orthogneiss units that formed a large part of the dome. The youngest zircon population (320–285 Ma) reflects derivation from late Carboniferous‐early Permian granite units in the axial zone of the Montagne Noire. This population appears first in the early Permian, persists throughout the Permian section and is accompanied by sandstone compositions dominated by feldspar, polycrystalline quartz and metamorphic lithic fragments. The most recent migmatization, magmatism and deformation occurred ca . 298 ± 2 Ma, at ca . 17 km depth (based on peak metamorphic conditions). Accordingly, these new provenance data, together with zircon fission‐track thermochronology, demonstrate that exhumation of the Montagne Noire core complex was rapid (1–17 mm year −1 ) and early (300–285 Ma), reflecting deep‐seated uplift in the southern Massif Central during post‐orogenic extension.